Nova - Yarros, Rebecca (Yarros, Rebecca. Renegades, 2017)
Landon Rhodes is the renegade they call Nova. He's a gorgeous, broody, tatted-up professional snowboarder and full time heartbreaker. A girl broke him once and that's why he's so reckless, so driven, so careless with his conquests.